Clinical Results and Serum Metal Ion Concentrations following Ceramic-on-Metal Total Hip Arthroplasty at a Mean Follow-Up of 60 Months. (8th March 2017) - Maurer-Ertl, W.; Pranckh-Matzke, D.; Friesenbichler, J.; Bratschitsch, G.; Holzer, L. A.; Maier, M.; Leithner, A.
Abstract : Background . Increased metal ion levels following total hip arthroplasty (THA) with metal-on-metal bearings are a highly debated topic. Local soft tissue reactions with chronic pain and systemic side effects such as neuropathy are described. The aim of the current study was to determine the serum metal ion concentrations of Cobalt (Co) and Chrome (Cr) after THA with a ceramic-on-metal (CoM) bearing. Patients and Methods . Between 2008 and 2010, 20 patients underwent THA using a CoM bearing. Clinical function was evaluated by standardized scores systems (Harris Hip Score and WOMAC Score) and radiological examination included X-rays. Patient's blood samples were obtained for metal ion analysis and correlation analysis was done between these results and implant position. Results . Overall, 13 patients with 14 CoM devices were available for the current series. The mean age at time of surgery was 61 years (range, 41 to 85). The postoperative follow-up ranged from 49 to 68 months (mean, 58). Metal ion determination showed mean concentrations of 3, 1 µ g/L (range, 0, 3–15, 2 µ g/L) for Co and 1, 6 µ g/L (range, 0, 1–5, 5 µ g/L) for Cr, respectively. A correlation between cup anteversion and Co and Cr concentrations was shown. Conclusion . The current series showed increments for Co and Cr following CoM THA. However, these levels are lower compared to metal ion concentrations in patients with metal-on-metal bearings and the international accepted threshold for revision of MoM devices. We recommend routine follow-up including at least one obligatory evaluation of serum metal ion concentrations and an MRI once to exclude local soft tissue reactions.